Chromosome preparation in fish: effects of fish species and larval age - Karami, Ali; Araghi, Peyman Eghtesadi; Syed, Mohd Arif; Wilson, Scott P. (Springer, 2015)
To date, several protocols have been developed to achieve clear and identifiable metaphase chromosome spreads from larvae of a single fish species. However, the efficiency of these protocols in more than one fish species has barely been compared within a single study. This work investigated the dependency of chromosome preparation parameters including colchicine concentration (0.01, 0.025, 0.05 %) and exposure duration (3, 5 h), hypotonic solution (distilled water, 0.075 M KCl solution), and Giemsa stain solution concentration (6, 8, 10, 11, 12, and 14 %) and incubation period (15, 30, 45, and 60 min) to two species of fish, the African catfish (Clarias gariepinus) and the zebrafish (Danio rerio) at different larval ages (0, 2, and 4 days post-hatch, dph). Results indicated that larval age, colchicine concentration and/or incubation time, and/or the type of hypotonic solution varied with fish species while staining the chromosomes with 11 % Giemsa solution for 45 min can be maintained regardless of the species or larval age. Interestingly, employing the selected values from diploid C. gariepinus experiment to prepare metaphase chromosomes from larvae of their triploid siblings proved to be efficient.